2014
DOI: 10.1515/jpm-2014-0108
|View full text |Cite
|
Sign up to set email alerts
|

Interinstitutional variations in mode of birth after a previous caesarean section: a cross-sectional study in six German hospitals

Abstract: There is substantial interinstitutional variation in mode of birth following previous caesarean section. This variation is in addition to regional patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…Multivariable analysis was used for the whole study group and for each country separately using random effects logistic regression models with the dependent variable "success of planned VBAC". Variations in labour and birth management for planned VBAC had been observed at the sites prior to the trial in Germany (Gross et al, 2015) and were accounted for by using a random effects term for all study sites. Multiple imputation (Stata "mi set" with fivefold imputation) was used for the variables "BMI", "married/living with partner", "health insurance", "cervical dilatation on admission" and "rupture of membranes" because of up to 14% missing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariable analysis was used for the whole study group and for each country separately using random effects logistic regression models with the dependent variable "success of planned VBAC". Variations in labour and birth management for planned VBAC had been observed at the sites prior to the trial in Germany (Gross et al, 2015) and were accounted for by using a random effects term for all study sites. Multiple imputation (Stata "mi set" with fivefold imputation) was used for the variables "BMI", "married/living with partner", "health insurance", "cervical dilatation on admission" and "rupture of membranes" because of up to 14% missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Euro-Peristat, 2018; Gross et al, 2015;Macfarlane et al, 2016;Mikolajczyk et al, 2013). A lack of consensus about optimal labour management methods may contribute to the variations (Gross et al, 2015). Scott et al (2014) recommended an intrapartum management similar to parturients without a c-section in history.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…The key features of note are that the publicly funded model of care is predominantly medically led and that the women give birth in a hospital setting. These factors are important when considering the national CS rate for any country, since significant variations in CS rates have been identified at the unit level, depending on whether the woman attends the public system or utilises health insurance to attend an obstetrician privately [5]. …”
Section: Methodsmentioning
confidence: 99%
“…In the absence of a robust justification of these increasing rates, an exploration of clinicians’ attitudes to CS as a mode of birth is required [2, 57], since an understanding of the non-medical factors associated with the decision to perform a CS are becoming more important. These factors include maternal requests [8] and provider attitudes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such information is not available in our registry, but may often be obtained directly from the pregnant woman, or from her medical records. Gross et al performed a study on variations in mode of delivery after a previous CS in six German hospitals, and found a substantial variation between institutions, in addition to a variation in regional patterns. In our previous study on VBAC prediction, we found that delivery ward characteristics (emergency CS in TOL, and elective repeat CS rates, respectively) significantly influenced VBAC rates.…”
Section: Discussionmentioning
confidence: 99%